Effects of Anthropogenic Impact on Water Quality in Bertam Catchment, Cameron Highlands, Malaysia - Islam, Mir Sujaul; M. G., Rasul; Fadzil, Mat Yahaya; Lubna, Alam; Mazlin, Mokhtar (National Institute of Ecology, 2015)
Along the Bertam Catchment, Cameron Highlands, Malaysia, a study was conducted based on water sampling from different points. The study was done to investigate the spatial variability of the physico-chemical parameters with reference to varying anthropogenic activities. A total of sixteen water quality parameters were analyzed. Analytical results showed that electrical conductivity and total dissolved solids exhibited similar spatial variations and were higher in Lower Bertam than Upper. Total suspended solids concentrations ranged widely and were much higher than standards, due to higher soil erosion and sedimentation. Nutrient variables showed significance spatial variations influenced by anthropogenic activities. Among the tributaries, Sungai Jasar showed higher variations in almost all parameters than others. This study demonstrates that the water quality at stations around urban and agricultural areas is becoming deteriorated. Improvement of domestic waste treatment methods, agricultural practices and unplanned land clearing is pre-requisite to preserve the water quality from further deterioration.